ANALISIS CITRA MEREK, PERIKLANAN, WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK WARDAH di UNIBA SURAKARTA - Furaida Nur Afifah; Bambang Mursito; Rochmi Widayanti (JURNAL ILMIAH EDUNOMIKA, 2019)
This research aim to determine the effect of brand image, advertising and word of mouth on Wardah cosmetic purchasing decisions in UNIBA surakarta. This research uses quantitative research type. Population of this research is UNIBA female students majoring in economics and taken 100 people as samples. Sampling technique using purposive sampling method. Data were obtained by giving questionnaires to student who use or ever use Wardah cosmetic at least once. Data analysis technique using multiple linier regression. The result of data analysis found that brand image, advertising and Word of mouth have effect to purchasing decision simultaneously or partially. Keywords: Brand Image, Advertising, Word Of Mouth, Purchasing Decisions